Modelling policy implementation performance of public primary school leaders in Malaysia - Noryati Alias
A policy is central to the development of a country. Given that an educated population is essential for the wealth of a country, the government creates a robu t educational system, reforms, and policies for its people. Numerous educational policies have been planned and implemented in Malaysia. Although the government's expenditure in ensuring the achievement of the policy goals and outcomes i high, educational issues such as the unsatisfactory performance of students in international assessments and the low domination of the higher-order thinking skills among students are increasing. School leaders are important policy actors where their policy implementation performance depends on the context, attitude, and actions. This study investigate the ignificance of policy content meaningfulness and public leadership towards policy implementation performance of the school leaders. Policy acceptance and commitment are mediating variables to explain the relationship between policy content meaningfulnes and public leader hip towards the policy implementation performance. The target population of this study are the Senior Leaders Team at the public primary schools in Malaysia, namely the Headmaster, and three Senior Teacher Assistants: Academic, Student Affairs, and Co-Curriculum. Clustered random sampling is used to select the respondents. The questionnaire utilised validated multiple-items that are adapted and customi ed to uit the context of the study. The respondents react to a 10- point int rval cal . For each public primary school selected, four questionnaires were placed in the school's mailbox located in the District Education Department offices. The respondents returned the completed questionnaire by po ting in a given selfaddressed stamped envelope. The data gathered were analysed using Structural Equation Modelling ( EM) through IBM SP S 21.0 and IBM SPSS AMOS 21.0. The results confirm the hypotheses to determine the direct and significant effect among the con tructs. Moreover. th tudy shows that that policy acceptance and commitment partially mediate the relation hip between the constructs of policy content meaningfulness, public leadership, and policy implementation performance. The structural model indicate that the policy implementation performance construct has 47% of total variance explained by the policy acceptance, policy content meaningfulness public leadership, and commitment. This research aimed to explain the influence of policy content meaningfulness, public leadership, policy acceptance, and commitment towards policy implementation performance. Based on the quantitative analysi of the Structural Equation Modelling, it can be concluded that policy content meaningfulness, public leadership, policy acceptance, and commitment are important constructs in d veloping a model for policy implementation performance. The model that includes the con truct of policy content meaningfulness, public leadership, policy acceptance, and commitment adequately demonstrated to be capable of assisting the Senior Leader Team in public primary schools in Malaysia to implement educational policies uccessfully. Furthermore, this model is a reliable source of information that could be appraised by researchers and professional practitioners of educational policies for futur research in policy implementation performance.